Anisotropic Turbulent Kinetic Energy Budgets in Compressible Rectangular Jets - Kalyani Bhide; Shaaban Abdallah (Aerospace, 2022)
Turbulence is governed by various mechanisms, such as production, dissipation, diffusion, dilatation and convection, which lead to its evolution and decay. In high-speed flows, turbulence becomes complicated due to compressibility effects. Therefore, the goal of the current work is to characterize these mechanisms in rectangular supersonic jets by directly evaluating their contributions in turbulent kinetic energy (TKE) budget equation. The budgets are obtained using high-fidelity Large Eddy Simulations that employ WALE subgrid-scale model. Jet nearfield data are validated with PIV experimental measurements, available from the literature, which include mean flow and second-order statistics. To ensure spatial resolution and temporal convergence of higher-order statistics, qualitative performance metrics are presented. The results indicate that TKE production is the major source term, while pressure-dilatation term acts as a sink throughout the development of the jet. The diffusion term has the highest contribution from triple-velocity correlations, followed by pressure diffusion and molecular diffusion. Subgrid-scale diffusion and dissipation are also evaluated and their contributions are minimal. Each term is presented on both minor and major axis plane and reveals asymmetry in the statistics. A detailed explanation of budget contributions is provided, leading to the mechanisms responsible for the anisotropy of TKE.